2017
DOI: 10.1167/17.11.14
|View full text |Cite
|
Sign up to set email alerts
|

Chinese-character crowding—I. Effects of structural similarity

Abstract: Crowding impedes the identification of flanked objects in peripheral vision. Prior studies have shown crowding strength decreases with target-flanker similarity. Research on crowding in Chinese-character recognition has been scarce in the literature. We aimed to fill the research gap by examining the effects of structural similarity on Chinese-character crowding. Regularity in within-character configuration, i.e., orthographic legality, of flankers was manipulated in Experiment 1. Target-flanker similarity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In addition, what causes the polynomial trendline to be unpredictable in certain patterns of variation in viewing distance? Is it in uenced by the shape of the Chinese characters, as reported in previous research (Cheung & Cheung, 2017), or by the number of strokes? us, the methods used by the current study require modi cation to further assess these issues such as by collecting data on gaze time per character.…”
Section: Comparison Of Eoretical and Observed Valuesmentioning
confidence: 83%
“…In addition, what causes the polynomial trendline to be unpredictable in certain patterns of variation in viewing distance? Is it in uenced by the shape of the Chinese characters, as reported in previous research (Cheung & Cheung, 2017), or by the number of strokes? us, the methods used by the current study require modi cation to further assess these issues such as by collecting data on gaze time per character.…”
Section: Comparison Of Eoretical and Observed Valuesmentioning
confidence: 83%
“…Research has demonstrated that Visual Expertise and Crowding 23 configural information can be important for processing Chinese characters (e.g., Chen et al, 2013;Wong et al, 2012); inversion disrupts configural processing and causes impaired Chinese character recognition (Kao et al, 2010). Consequently, the intact global representations of the upright Chinese characters should induce a larger crowding effect on target face categorization compared to the inverted ones in native Chinese readers (though see Cheung & Cheung, 2017 for data suggesting that target-flanker similarity does not affect crowding strength in all cases). On the contrary, for non-Chinese readers, unfamiliar Chinese characters are meaningless objects when presented either upright or inverted, and thus should cause no difference in crowding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggested visual crowding to be a critical condition that affects reading rates (Pelli et al, 2007). Crowding severely affected the peripheral vision of children and adult readers (Gori and Facoetti, 2015;Strappini et al, 2017) and slowed down reading processing (Cheung and Cheung, 2017). In addition, the crowding effect was particularly strong in dyslexic readers (Martelli et al, 2009).…”
Section: Introductionmentioning
confidence: 94%